The Effect of Kompa Media (Science Comics) on the Predicting Skills of Class V Students in Elementary Schools: Pengaruh Media Kompa (Komik Ipa) Terhadap Keterampilan Memprediksi Siswa Kelas V di Sekolah Dasar - Yeni Windah Sari; Enik Setyawati (Academia Open, 2022)
The purpose of this study was to determine the effect of science comics media on the predicting skills of fifth grade students at Simogirang 1 Prambon Elementary School. Predictive skills have indicators suggesting what might happen. The research method used is experimental quantitative. This type of research is a one-group retest posttest with written test instruments and treatment, namely science comics media which includes material on the nature and form of objects in theme 7. The written test is obtained from students' answers which refer to the material properties and forms of objects with a total of 7 items, The first step is a written pretest, the second is a treatment, and the last is a posttest. The results of the research data from the results of the t-test known that the value of sig(-2 failed) was 0.000˂0.05. That is, the science comic media can be said to have a big influence on the predicting skills of fifth grade students at SD Negeri Simogirang 1 Prambon. This is indicated by the Eta Squared test of 95% and the remaining 5% is influenced by variables not examined.